The Incoherence Problem in the Many-Worlds Interpretation of Quantum Mechanics - Rubio Juan, María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The Many Worlds Interpretation of Quantum Mechanics has been faced since its conception with the problem of how to reconcile the probabilistic nature of quantum theory with a deterministic description of the Universe in which all possibilities are actualised. This paper seeks to present the status of the problem through the solutions proposed by Lev Vaidman and David Deutsch and to relate them, as well as to present probability as an epistemological postulate, in accordance with the subjectivistic interpretation.